A survey of mimetid spiders (Araneae, Mimetidae) from Central Guizhou Province, China - Jianshuang Zhang; Haoshen Zhang; Jinxin Liu; Hao Yu; Xiang Xu (Zoosystematics and Evolution)
A survey of the mimetids of Central Guizhou Province, China, is presented. A total of five species are addressed, raising the number of species of the genus Mimetus Hentz, 1832, known from this province from four to eight, making Guizhou the province with the most Mimetus species in China. Two of the taxa are new species: M. guiyang J. S. Zhang, Yu & Xu, sp. nov. and M. lanmeiae Liu, Yu & Xu, sp. nov., both from Guiyang City, provincial capital of Guizhou. The other three known species include two new records from Guizhou, M. caudatus Wang, 1990, and M. sinicus Song & Zhu, 1993, as well as a species, M. testaceus Yaginuma, 1960, that was previously recorded from the province. The female of M. caudatus is described for the first time, based on the new material from Duyun City. Detailed descriptions, diagnoses, and photographs of the two new species and M. caudatus, as well as photographs of M. sinicus and M. testaceus, are provided. The DNA barcodes of M. lanmeiae sp. nov., M. sinicus, and M. testaceus were obtained for species delimitation, matching of sexes, and future use.